Interprofessional Competency Toolkit for Internationally Educated Health Professionals: Evaluation and Pilot Testing. Issue 3 (2017) - Arain, Mubashir; Suter, Esther; Hepp, Shelanne; Nanayakkara, Shyama; Harrison, Elizabeth L.; Mickelson, Grace; Bainbridge, Lesley; Grymonpre, Ruby E.
Abstract : Introduction: Internationally Educated Health Professionals (IEHPs) constitute a major health care workforce in Canada. Interprofessional education is particularly important for IEHPs to integrate into the Canadian health care system. We designed an online interprofessional education curriculum for IEHPs. The curriculum is designed to cover the six interprofessional competency domains defined in the Canadian Interprofessional Health Collaborative National Interprofessional Competency Framework. In this article, we are presenting findings from the pilot testing of the curriculum with a cohort of IEHPs and educators. Methods: We conducted surveys and interviews with IEHPs and educators from four provinces (British Columbia, Alberta, Saskatchewan, and Manitoba). We aimed to include seven healthcare professionals: licensed practical nurses, registered nurses, registered psychiatric nurses, pharmacists, physicians, occupational therapists, and physical therapists. We also used a pre- post- self-assessment tool and a set of reflective questions to measure the effectiveness of the curriculum. Results: Thirty IEHPs and five educators reviewed the online curriculum and participated in this evaluation. Postintervention confidence scores for all items under the role clarification and patient-centered care domains increased significantly (P = <0.01) after module completion. The scores also increased for most questions in team functioning, collaborative leadership, and communication domains. The postassessment scores increased for only half of the questions in conflict management domains. Participants agreed with the appropriateness of the content in terms of language, scenarios, and cultural aspects covered in the online curriculum on interprofessional education. Discussion: The content of the curriculum improved IEHPs' understanding of interprofessional collaboration in Canada. The interprofessional curriculum is a creative and useful resource to improve collaborative practice among internationally educated health professionals in Canada.